Rationale for extent of operation choice in rectal cancer - Nikitenko, R.; Kosovan, V.; Vorotyntseva, K.; Koichev, E. (Journal of Education, Health and Sport, 2021)
Introduction. Colorectal cancer (CRC) remains relevant occupying one of the leading places in morbidity and mortality among oncological diseases. It reaches 13.5% in the structure of tumor diseases tending to increase. The aim of the work to improve the choice of surgical treatment management and reduce the number of intraoperative and postoperative complications in rectal cancer patients. Materials and methods. 184 operated patients with rectal cancer (RC) were divided into 2 groups: 1 group (patients with stage I RC (T1-2N0M0) and 2 group (stage II RC (T3N0M0)) who were carried out intraoperative detection and examination of sentinel lymph nodes. The volume and surgical approach depended on the stage and the presence of metastases (MTS). The average period of postoperative observation was 12–60 months, taking into account early (purulent-septic complications, bleeding, intestinal perforation) and distant (recurrence of rectal cancer) complications. Results. The patients of the 1 group had no MTS lesions of sentinel lymph nodes, due to this fact the surgical intervention was limited to transanal microsurgery. Among the complications were the following: bleeding – 2.2%; intraoperative perforation of the intestinal wall – 5.6%. No purulent-septic cases, no recurrences of rectal cancer were detected. In group 2, of 94 patients, 36 (38.3%) had MTS detected intraoperatively in sentinel lymph nodes which required a low anterior rectal resection with total mesorectomectomy. Among the complications was bleeding – 6.3%. No intraoperative perforations of the intestinal wall and no purulent-septic complications were detected. Recurrence of rectal cancer was detected in 12 (13.8%) patients. Conclusions. Performing transanal endoscopic resections in patients with RC I and especially stage II is possible only under the conditions of mandatory intraoperative staining and emergency histological examination of "sentinel" lymph nodes. The extent of surgical intervention is determined on the operating table based on the results of an emergency histological examination. When MTS lesions of the mesorectal "sentinel lymph nodes" are detected, the operation should be continued with mandatory mesorectomectomy.